Emerging trends and hot spots in subacute thyroiditis research from 2001 to 2022: A bibliometric analysis - Xu, Cheng; Jiang, Rui; Liu, Jiang-yu (Frontiers in Endocrinology, 2023)
Background: Subacute thyroiditis (SAT) is the most common self-limiting thyroid disease causing pain, accounting for approximately 5% of all clinical thyroid abnormalities. There have been numerous clinically noteworthy results in this area over the last 20 years. However, no article has comprehensively assessed the relavent literature to yet. In order to provide light on the dynamic nature of scientific advancement and aid researchers in gaining a global perspective while examining development hotspots and trends, we conducted a bibliometric analysis of SAT. Methods: SAT-related articles and reviews from 2001 to 2022 were retrieved from the Science Citation Index-Expanded of Web of Science Core Collection(WoSCC). CiteSpace and Vosviewer were used to analyze current research trends and hotspots in this field. Results: A total of 568 studies associated with SAT research were published in 282 academic journals by 2,473 authors in 900 institutions from 61 countries/regions. USA occupied the leading role and was the most frequently involved country in international cooperation. The leading institution was University of Missouri System, and the most productive researcher was Braley-Mullen H. Thyroid published the most papers, with 36 publications. The most co-cited paper was “Clinical features and outcome of subacute thyroiditis in an incidence cohort: Olmsted County, Minnesota, study”(by Fatourechi V, 2003). Analysis of keyword co-occurrence, clusters, and bursts indicated that the researchers were interested in the incidence of SAT, clinical characteristics, clinical studies of diagnosis and treatment, as well as the influence of COVID-19 on SAT. Conclusion: This bibliometric analysis conducted a thorough review of the SAT research. Prevalence, clinical characteristics, diagnosis and treatment of SAT under the influence of COVID-19 epidemic are current research hot spots. However, there is still a need for further study and global collaboration. Our findings can help researchers grasp the status of the research of SAT and quickly identify new directions for future research.